Management and treatment of decompensated hepatic fibrosis and severe refractory Schistosoma mansoni ascites with transjugular intrahepatic portosystemic shunt - Santo, Maria Cristina Carvalho do Espírito (2022)
This study aimed to report the first case of a patient with hepatosplenic schistosomiasis mansoni, refractory ascites and portal vein thrombosis treated with a transjugular intrahepatic portosystemic shunt (TIPS), at the Instituto de Radiologia, Hospital das Clinicas, Faculdade de Medicina, Universidade de Sao Paulo, Brazil. After the procedure, the patient recovered favorably and progressed with portal pressure reduction and no deterioration of the liver function. Endovascular shunt modification is a conservative medical approach that often helps in reducing symptoms significantly, making it a less invasive and a safer alternative to liver transplantation for the treatment of schistosomiasis with portal hypertension.